Analisis Penggunaan Istilah Bahasa Indonesia di Kalangan Generasi Z (Studi Kasus pada Mahasiswa Bisnis Digital UNIMED) - Nasution, Fatmawati; Nada, Qatrun; Ratisya Dwina, Shezy; Fathiya Amira, Tengku; Simanungkalit, Wahyu; Rosmaini (UNIVERSITAS SERAMBI MEKKAH, 2024)
This study aims to analyze the use of language terms in relation to the use of Bahasa Indonesia in the communication of students in the Digital Business program at Universitas Negeri Medan. A total of 20 students from the Digital Business program at Universitas Negeri Medan were selected as the sample after a screening process. The analysis results found that the use of Bahasa Indonesia among Generation Z students in the Digital Business program at Universitas Negeri Medan is proven to be very high, with a score of 5 on almost all items in the questionnaire. The implications of this study may provide input for language planning initiatives and communication strategies that can effectively interact and align with the preferences of Generation Z.